Immune mechanisms mediating the heterologous effects of BCG vaccination: a systematic review - Torracinta, Louis; Gogichadze, Nino; Tanner, Rachel (Frontiers in Immunology, 2025)
IntroductionBCG vaccination can have heterologous or non-specific effects (NSE) that confer resistance against pathogens other than its target Mycobacterium tuberculosis, but the underlying mechanisms are not fully understood.MethodsWe conducted a systematic review synthesising existing literature on immune mechanisms mediating the heterologous/NSE of BCG. Searches were conducted using MEDLINE and Scopus.Results1032 original records were identified, of which 67 were deemed eligible. Several potentially relevant immune pathways were identified, although there may be variation by pathogen. Recent studies have focused on trained immunity whereby innate cells, or the hematopoietic stem and progenitor cells from which they are derived, undergo epigenetic and metabolic reprogramming allowing them to respond more effectively to antigen exposures unrelated to the original stimulus. However, other processes such as granulopoiesis and cross-reactive adaptive immunity may also play a role. Heterologous immunity and NSEs may be influenced by several endogenous and exogenous variables.DiscussionWe discuss the quality of available data, the importance of understanding mechanisms of heterologous protection, and its implications for vaccination strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023400375, identifier CRD42023400375.